CYP11A1 Upregulation Leads to Trophoblast Oxidative Stress and Fetal Neurodevelopmental Toxicity That can be Rescued by Vitamin D - Wang, Xiang; Li, Mengxue; Zhang, Xueguang; Li, Yaqian; He, Guolin; Dinnyés, Andras; Sun, Qun; Xu, Wenming (Frontiers in Molecular Biosciences, 2021)
During normal pregnancy, the placental trophoblast secretes a variety of steroid hormones and participates in the regulation of maternal physiological functions and fetal development. The CYP11A1 gene encodes the cholesterol side-chain cleavage enzyme P450scc, which catalyzes the production of pregnenolone from cholesterol, which is the first step in the synthesis of all steroid hormones. Under the influence of genetic susceptibility and certain environmental factors, such as drugs and toxins, the expression of CYP11A1 can be upregulated, thereby affecting steroid metabolism and physiological functions in trophoblast cells, as well as fetal development. Here, we demonstrate that upregulation of CYP11A1 in the BeWo cell line triggers excessive mitochondrial oxidative stress, leads to mitochondrial damage and interleukin-6 release, and contributes to the inhibition of proliferation and DNA damage in neuronal stem cells (NSCs). Furthermore, oxidative stress and inflammation can be ameliorated by vitamin D3 in a dose-dependent manner, thereby facilitating the rescue of NSC impairment. Our findings reveal the underlying mechanism in which upregulation of CYP11A1 is detrimental to the physiological function of trophoblasts and demonstrate the beneficial effects of vitamin D supplementation in preventing placental and neurodevelopmental damage associated with CYP11A1 upregulation during pregnancy.